Zinc oxide thin film transistors using MgO-Bi1.5Zn1.0Nb1.5O7 composite gate insulator on glass substrate - Cho, Nam Gyu; Kim, Dong Hun; Kim, Ho-Gi; Hong, Jae-Min; Kim, Il-Doo (ELSEVIER SCIENCE SA, 2010)
We report on high mobility ZnO thin film transistors (TFTs) (<5 V), utilizing a room temperature grown MgO-Bi1.5Zn1.0Nb1.5O7 (BZN) composite gate insulator on a glass substrate. 30 mol% MgO added BZN composite gate insulators exhibited greatly enhanced leakage current characteristics (similar to<2 x 10(-8) A/cm(2) at 0.3 MV/cm) due to the high breakdown strength of MgO, while retaining an appropriate high-k dielectric constant of 32. The ZnO-TFTs with MgO-BZN composite gate insulators showed a high field-effect mobility of 37.2 cm(2)/Vs, a reasonable on-off ratio of 1.54x10(5), a subthreshold swing of 460 mV/dec, and a low threshold voltage of 1.7 V. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: ROOM-TEMPERATURE; DIELECTRICS